Agomelatine Demonstrates Broad Efficacy in Depression - Cunningham, Muriel (MD Conference Express, 2007)
Agomelatine, a melatonergic agonist and a selective 5-HT2c antagonist, is a novel antidepressant in development for major depressive disorder. This article discusses a meta-analysis of pooled data from three clinical studies. The objective of the meta-analysis was to determine whether gender or baseline severity of depression had any influence on agomelatine efficacy.